FROM CAPACITIES TO MOTOR ABILITIES: FROM A SYSTEMIC HOLISTIC TRANSDISCIPLINARY APPROACH - Chávez Cáceres, María Luz (2014)
It approaches the motor ontogenesis in all its dynamics. It conceives human motor learning as a functional system, where capacities, skills, habits and abilities, constitute the integral elements of this system. It analyzes in detail each one of the «sections» of the dialectic spiral which its evolution becomes, from its departure point: the capacity, to its destination the ability. The last one is identified as the maximum level of profit or experience at which the apprentice arrives after a long process from formation, consolidation and improvement. It considers the process of formation of abilities from a holística and transdisciplinar perspective. Even though one talks about the field of the sport motor action and intends to explain the process of learning and motor improvement, postulates that the underlying theory can generalized to any type of learning, independently of the discipline, the condition or the age of the subject-apprentice.